Analisis Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Industri Konstruksi Yang Terdaftar di Bursa Efek Indonesia Periode 2012 – 2016 - Venny Junica Utami (Universitas Batanghari, 2018)
The results of this study indicate that Financial Performance, Risk Management and Working Capital Management Against Stock Price of Construction Industry in Indonesia Stock Exchange period 2012-2016 with the number of Fhitung 12,441 and Ftabel of 2.71, it can be seen that Fcount> Ftable is 12,441> 2, 71, meaning there is a significant influence between earnings per share (EPS), price earning ratio (PER), return on equity (ROE), bi rate and cash conversion cycle (CCC) simultaneously to stock prices while the value of t arithmetic EPS of 5.494 and ttabel 1.72472 from the comparison then it can be known t count <ttabel (5,494 <1,72472). The conclusion is that all independent variables have significant effect on dependent variable at α = 5% or 0,05 and F test criterion by comparing Fcount 12,441 and Ftabel 2,71, it can be seen that Fcount> Ftable is 12,441> 2,71 , meaning there is a significant influence between earnings per share (EPS), price earning ratio (PER), return on equity (ROE), bi rate and cash conversion cycle (CCC) simultaneously to stock price in property and real estate industry in 2012 -2016. Keyword: financial performance, stocks, stock exchange